2013
DOI: 10.1063/1.4791713
|View full text |Cite
|
Sign up to set email alerts
|

Novel microwave near-field sensors for material characterization, biology, and nanotechnology

Abstract: The wide range of interesting electromagnetic behavior of contemporary materials requires that experimentalists working in this field master many diverse measurement techniques and have a broad understanding of condensed matter physics and biophysics. Measurement of the electromagnetic response of materials at microwave frequencies is important for both fundamental and practical reasons. In this paper, we propose a novel near-field microwave sensor with application to material characterization, biology, and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Figure 21 gives an example of transformation of the MDM spectrum due to dielectric loadings with different permittivity parameters. An insert shows a microwave microstrip structure (sensor) with a MDM ferrite disk and a sample under investigation [50]. In this figure, one can observe the shift of the MDM spectrum to lower frequencies.…”
Section: Novel Microwave Near-field Sensors For Materials Characterizamentioning
confidence: 93%
See 4 more Smart Citations
“…Figure 21 gives an example of transformation of the MDM spectrum due to dielectric loadings with different permittivity parameters. An insert shows a microwave microstrip structure (sensor) with a MDM ferrite disk and a sample under investigation [50]. In this figure, one can observe the shift of the MDM spectrum to lower frequencies.…”
Section: Novel Microwave Near-field Sensors For Materials Characterizamentioning
confidence: 93%
“…[21,43,50] it was shown that dielectric samples loading a ferrite disk can cause strong transformations of the MDM spectra. These transformations are exhibited by two factors for an entire MDM spectrum: (a) the frequency shift of the spectrum and (b) broadening of the spectrum.…”
Section: Novel Microwave Near-field Sensors For Materials Characterizamentioning
confidence: 99%
See 3 more Smart Citations